Cannabidiol in conjunction with clobazam: analysis of four randomized controlled trials. (22nd October 2020) - Gunning, Boudewijn; Mazurkiewicz‐Bełdzińska, Maria; Chin, Richard F. M.; Bhathal, Hari; Nortvedt, Charlotte; Dunayevich, Eduardo; Checketts, Daniel
Abstract : Objectives: To assess the efficacy and safety profile of add‐on cannabidiol (CBD) in patients with Lennox–Gastaut syndrome (LGS) and Dravet syndrome (DS) on clobazam and in the overall population of four randomized, controlled phase 3 trials. Methods: Patients received plant‐derived, highly purified CBD medicine (Epidiolex ® in the USA; Epidyolex ® in Europe; 100 mg/ml oral solution) at a dose of 10 or 20 mg/kg/day, or placebo for 14 weeks. A subgroup analysis of patients on clobazam and meta‐analysis by syndrome were conducted. The primary endpoint was percentage reduction in primary seizure type during the treatment period. Results: 396 patients with LGS (49% on clobazam) and 318 patients with DS (64% on clobazam) were included. CBD treatment resulted in a reduction in primary seizure frequency vs placebo in the overall population (treatment ratio [95% confidence interval]: LGS, 0.70 [0.62‐0.80]; DS, 0.71 [0.60‐0.83]) and in patients receiving clobazam (LGS, 0.56 [0.47‐0.67]; DS, 0.63 [0.52‐0.77]). The antiseizure efficacy of CBD was also demonstrated across other endpoints vs placebo (≥50% responder rate, total seizure frequency, number of seizure‐free days, and Subject/Caregiver Global Impression of Change scores) in the overall populations and in patients receiving clobazam. There were higher incidences of somnolence and sedation in patients on CBD and clobazam. Most incidences of elevated transaminases occurred in patients on concomitant valproate and, to a lesser extent, clobazam. Conclusions: Add‐on CBD was effective in reducing seizures in the overall populations and in conjunction with clobazam. Somnolence and sedation occurred more frequently in patients on CBD and clobazam.